256. LOCAL CONTROL OF HEPATIC/PULMONARY OLIGOMETASTASIS IS EFFECTIVE IN EGJ ADENOCARCINOMA. (24th September 2022) - Imamura, Yu; Kanie, Yasukazu; Maruyama, Suguru; Sakamoto, Kei; Kuriyama, Kengo; Okamura, Akihiko; Kanamori, Jun; Watanabe, Masayuki
Abstract: This study investigated the clinicopathological features of distant metastasis of esophagogastric junction (EGJ) adenocarcinoma. Survival benefit of local management was also examined in the patients with hepatic or pulmonary oligometastasis. Among a total of 449 cases of Siewert type I-II surgically resected EGJ adenocarcinoma (2005–2020), 166 cases with distant metastasis were eligible. Examining 22 cases with liver metastasis alone who treated in our hospital, liver-resected cases (N = 13) experienced better outcomes (mOS; 48 M for resection, vs. 8.1 M for those without resection, P = 0.0002). More favorable outcome was observed in the patients with 1–3 nodules (N = 11, P = 0.0023). Regarding lung metastasis alone, systemic chemotherapy was applied to bilateral multiple nodules, otherwise, local control including resection or stereotactic irradiation was selected. The mOS in the patients who underwent local control was significantly longer than that of chemotherapy (44 M for resection vs. 17 M for chemotherapy, P = 0.035). Tumor location or histological type of the primary tumor was associated with organ sites of distant metastasis. Local management conferred survival benefit in the patients with oligometastasis in liver or lung alone.